Normas de selección deportiva para la iniciación del judo ecuatoriano en edades entre 8-11 años - Egas Romo, S. R.; Romero Frómeta, C. E. (Lecturas: Educación Física y Deportes, 2018)
Judo is a combat sport with the objective of defeating an opponent in a tatami by applying a combat for points, for which it is necessary to establish several national parameters for the sport selection. The research objective is to elaborate standards of detection and massive sports selection for initiation in Ecuadorian Judo between 8 to 11 years of age. The research is descriptive and analytical. A sample of 58 (female) and 69 (male) judokas between the ages of 8-11 years (both sexes) is studied, applying 11 sports performance indicators to conform the norms based on the percentiles application (10, 20, 30, 40, 50, 60, 70, 80, 90). The research objective is fulfilled, recommending to expand the sample size to generalize the results in Ecuador.